(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Acetabular fractures often result from severe trauma, and incorrect treatment can lead to serious complications. Objectives: 1. Evaluate the effectiveness of surgical treatment for acetabular fractures. 2. Determine the incidence of complications related to acetabular fracture surgery. Subjects and Methods: - Patients diagnosed with and treated surgically for acetabular fractures due to trauma. - Fracture types included: • Displaced intra-articular fragments. • Marginal rim fractures. • Wide articular surface fractures. • Instability fractures Results: Over a 5-year period (2015–2020), with assistance from Cho Ray Hospital, Thong Nhat Dong Nai General Hospital performed surgical procedures on 21 cases of acetabular fractures, with an average follow-up time of 28.6 months. Excellent and very good results were achieved in 16 cases (76.2%). Fair results in 3 cases (14.2%). Poor results in 2 cases (9.5%). Conclusions: The earlier the surgery, the better the results. Early surgical management of acetabular fractures, with minimal articular cartilage damage, precise reduction, and avoidance of complications, leads to good outcomes. In other words, the more anatomically precise the acetabular reduction, the better the achieved functional outcomes.